Pengaruh Pendidikan Kesehatan tentang Stunting terhadap Pengetahuan Remaja di Desa Teluti Baru Kecamatan Tehoru - Maritje S. J. Malisngorar; Idham Soamole; Wa Ode Junita (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Stunting is a condition of short or very short body which is a problem in Indonesia, a description of the status of chronic malnutrition during growth and development since the beginning of life. One indicator to see the quality of nutrition in adolescents is by measuring body height and then presenting it according to the World Health Organization with a height-for-age (TB/U) z-score value of less than -2 standard deviation (SD) based on growth standards. To identify the influence of health education about stunting on adolescent knowledge in Teluti Baru Village, Tehoru District. Using a pre-experimental design and a sample size of 66 students using instruments in the form of questionnaires and leaflets. The analysis used is the Wilcoxon T-test. It was found that there was an influence of education on the level of knowledge of teenagers regarding stunting in Teluti Baru Village, Kec. Tehoru (p-value = 0.000). There is the influence of health education before and after being given stunting education treatment for adolescents in the village of Teluti Baru, sub-district. Tehoru